Research Methods in Teaching Listening Skills Utilizing Technology Media - Maulina Maulina; Risna Ladjagang; Rahmat Nasrullah; Alfredo M. Esteban Jr; Hastianah Hastianah; Herianah Herianah (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhhammadiyah kendari, 2022)
The language research method is an area of interest for many language researchers. Reviewing the latest research methods provides rich potential contributions for learning sources for a greater understanding and productivity to conduct novel and essential research, especially in teaching listening skills utilizing technology media. Therefore, this paper elaborates on the research methods used in teaching listening skills using technology media. The elaboration is formulated from the research methods used by journal article writers worldwide. Sixteen international journal articles and four national journal articles are taken as the corpus of the study are investigated using grounded theory analysis. Among the found research methods are case study, ethnography research, phenomenological study, grounded theory, narrative, content analysis study, document analysis, descriptive qualitative, pre-experimental research, quasi-experimental research, true experimental research, correlational research, ex-post-facto, survey research, classroom action research, collaborative action research, and mixed-methods. However, due to the limited space, the paper will only describe five popular methods in teaching listening skills utilizing technology media for the last ten years, including experimental research, classroom action research, survey research, case study, and descriptive qualitative research. The description of each method is supported by examples found in international and national journal articles published worldwide